Electricity Production and Characterization of High-Strength Industrial Wastewaters in Microbial Fuel Cell - Cetinkaya, Afsin Y.; Ozdemir, Oguz Kaan; Demir, Ahmet; Ozkaya, Bestami (HUMANA PRESS INC, 2017)
Microbial fuel cells (MFCs) convert electrochemical energy into electrical energy immediately and have a big potential usage for the same time wastewater treatment and energy recovery via electro-active microorganisms. However, MFCs must be efficiently optimized due to its limitations such as high cost and low power production. Finding new materials to increase the cell performance and reduce cost for MFC anodes is mandatory. In the first step of this study, different inoculation sludges such as anaerobic gum industry wastewater, anaerobic brewery wastewater and anaerobic phosphate were tested, and MFC that was set up with anaerobic gum industry wastewater inoculation sludge exhibited the highest performance. In the second step of this study, various wastewaters such as chocolate industry, gum industry and slaughterhouse industry were investigated for anode bacteria sources. Several electrochemical techniques have been employed to elucidate how wastewaters affect the MFCs' performance. Among all the mentioned wastewaters, the best performance was achieved by the MFCs fed with slaughterhouse wastewater; this device produced a maximum power density of 267 mW.m(-2).
Keywords: Microbial fuel cell; Anode; Wastewater; Anaerobic sludge; WASTE-WATER TREATMENT; ENERGY RECOVERY; GENERATION; SLUDGE; PERFORMANCE; MEMBRANE; CATHOLYTE; ELECTRODE; REACTORS; CATHODE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology